Perancangan Aplikasi Game Edukasi Pengenalan Buah Siswa Berbasis Android Untuk Sekolah Dasar - Lumentut, Hence; Rumagit, Silviani; Karen Tuuk, Gabriela (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
The Educational Game Application of Fruit Design introduction for Elementary School and Android-based Kindergarten, is one of the android-based applications specifically designed for Education and also Games to introduce Fruits to PAUD and Kindergarten students to stimulate the learning process of students to have an interest in getting to know the fruits that are around us. This Android Educational Game Application is designed using a Prototype model system design approach which has the advantage of being able to work with a small team of even just one person, prototypes are also versatile in making a finished application and then shown to system users, whether it is in accordance with user needs or not, if not then adjustments will be made as necessary. To show the system and design of this application using the UML (Unified Modeling language) method which shows modeling diagrams and testing using Black Box Testing. Based on the results of this Educational Based Application, it shows that the game can be made to teach PAUD and TK students and can also stimulate interest in learning because it is equipped with games to test students' knowledge about the types of fruits that are around us.